Variable piezoelectricity of electrospun chitin. (1st September 2018) - Street, Reva M.; Huseynova, Tatyana; Xu, Xin; Chandrasekaran, Prashant; Han, Lin; Shih, Wan Y.; Shih, Wei-Heng; Schauer, Caroline L.
Graphical abstract: Highlights: A naturally-occurring electrospun biomolecule has been investigated for its native piezoelectricity. Using the common air-gap collection system, the chitin nanofibers demonstrated a 300% increase in mechanical strength and a 400% increase in piezoelectricity. The increase in crystallinity of the chitin fibers produced in the air-gap electrospinning process caused an increase in the piezoelectric response. Abstract: Investigations into the piezoelectricity of natural polymers is a continuing area of interest due to their potential role in the complex interplay of mechanical and electrical forces present in biological organisms. Their synthetic counterparts, when electrospun using the air gap electrospinning method, are known to have increased crystallinity and tensile strength as compared to randomly aligned nanofibers composed of the same constituent polymers. Using the air gap electrospinning method with the naturally-occurring, semi-crystalline polymer chitin, the nanofibers were determined to have a 300% increase in tensile strength over randomly collected ones. Additionally, a 400% increase in piezoelectric response in the aligned nanofiber chitin mats was measured. The increased tensile strength and piezoelectricity in aligned chitin nanofibers is a consequence of an increase in α-chitin crystallinity in the nanofibers induced by the air gap collection method.